(3GNJUGQ Ydhe GdMOjKs - (3GdMGaX ESeGYjd,J (B774 (3g` s ((3EHQGgje Hf eMeO Hf ehSi GdMhGQfi s)
(3ChdgG (B:s
(3bGd TjNfG ESeGYjd Hf cKjQ GdMeO ddg hSdGe Ydi YHGOg GdPjf GUWai CeG HYO aEf Yde GdMOjK GdfHhi Ydi bGFdg CaVd GdUdGI hGdSdGe bO GYJfi HGdcdGe ajg LeGYI ef GdMaGX s
(3BNQgG (B:s
(3EfeG jShZ GdGfJSGH Edi GdHdO EPG CbGe CQHY Sfjf aCcKQ hGddg SHMGfg hJYGdi CYde HGdUhGH s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs